Carolina Freyre de Jaimes, a century after his death A biographical approach (1844-1916) - Escala Araníbar, María del Carmen (2017)
A recent investigation about the writer Carolina Freyre de Jaimes and her discursive handling of the harangue of war has shown her role during the Peruvian war against Chile. This biographical approach, reconstructed with verified information in primary sources and in critical works, allows to understand the participation of Carolina Freyre in the cultural scene and in the national politics. It is argued that the influences of her husband Julio Lucas Jaimes favored her and enabled her to show her talent and be recognized as a writer.